Analisis Performa Important Matrix Pelayanan Perguruan Tinggi X - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2007)
Customer satisfaction constitutes the dominant factor in a business organimtionâs success. This research presents key factors affecting satisfaction and dissatisfaction and the strategy applied onto improving satisfaction in the X University. The data collected from 200 students selected by xddent sampling. The study reveal that students (customers) satisfied with facility to meet academic adviser, curriculum, course schedule, quality of course content, course material, administration seruices in the department, quality of laboratory equipment, and parking services. Students dissatisfied with surse inputting, library, academic access, administration service in the faculty and unroersity, classroom, teaching equipment, sanitation toilet room, responsiveness, and service simplicity. In order to increasing customerâs satisfaction, university must improve factor effect dissatisfaction factor. Keywords: customers, satisfaction, imxrtant peiforma matric